Seating arrangement and students’ behaviour in French language classroom: a qualitative case study in higher education in Malaysia - Riaz, Saira (RSIS International, 2025)
Several educators believed that the seating arrangement is a critical factor for learning performance. Seating arrangement is considered as a pivotal factor in giving positive learning outcomes and learning behaviour. Most of the educational literature addresses issues such as room temperature, room lighting, and acoustics (Conners, 1983, Granstrom, 1996). Fewer studies have been conducted on the classroom seating arrangement and its effects on students’ actions and learning (Haghighi and Jusan, 2012, Hoekstra et al., 2023). This paper examines the impact of seating locations on student classroom learning. Specifically, it examines the impact of seating on a) student learning behaviour b) student and teacher relationships c) attention d) student classroom participation. Active engagement and participation in the learning experience positively affects students' learning while promoting the use of higher order thinking skills (Flynn, Vermette, Mesibov and amp; Smith, 2009; McKeachie, 1990; Stronge, 2007). This study was conducted with an objective to compare two different types of seating arrangements: rows and circular in the traditional and modern French language classrooms.